2021
DOI: 10.1007/s10029-020-02364-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits of routine examination and synchronous repair of occult inguinal hernia during laparoscopic peritoneal dialysis catheter insertion: a single-center experience

Abstract: Purpose Occult inguinal hernias (IH) predispose peritoneal dialysis (PD) patients to the symptomatic IH formation after starting PD, which may cause complications. We conducted a retrospective study to assess the benefit/risk profile of routine laparoscopic examination for occult IH (RLEOH) with a synchronous repair in patients receiving PD catheter placement. Methods 432 patients were enrolled in this study. Patients with an internal hernia sac at all siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The incidence of catheter dysfunction was 31.8% with open surgery, 17.5% with basic laparoscopy, and only 4.4% with advanced laparoscopy [ 11 ]. For patients with cholecystitis and occult hernia, cholecystectomy and hernia repair can be performed during advanced laparoscopic PDC insertion to avoid postoperative infectious complications and hernia, which takes full advantage of laparoscopic procedure [ 12 , 13 ]. Different surgeons tend to set different numbers of laparoscopic ports.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of catheter dysfunction was 31.8% with open surgery, 17.5% with basic laparoscopy, and only 4.4% with advanced laparoscopy [ 11 ]. For patients with cholecystitis and occult hernia, cholecystectomy and hernia repair can be performed during advanced laparoscopic PDC insertion to avoid postoperative infectious complications and hernia, which takes full advantage of laparoscopic procedure [ 12 , 13 ]. Different surgeons tend to set different numbers of laparoscopic ports.…”
Section: Discussionmentioning
confidence: 99%
“…A study on managing open inguinal repair and PDC placement has been conducted. 10,21 Kou et al reported diagnosis of inguinal hernia using laparoscopic approach with open inguinal hernia repair. 10 However, in our study, laparoscopic PDC placement and laparoscopic inguinal hernia repair was performed utilizing a 1-cm incision and three incisions of 5-mm size.…”
Section: Discussionmentioning
confidence: 99%
“…10,21 Kou et al reported diagnosis of inguinal hernia using laparoscopic approach with open inguinal hernia repair. 10 However, in our study, laparoscopic PDC placement and laparoscopic inguinal hernia repair was performed utilizing a 1-cm incision and three incisions of 5-mm size. This eliminates two admissions and operations and reduces cost and risk of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations